Legal Innovation in Religious Courts: The Potential Utilization of Artificial Intelligence (AI) in Resolving Contemporary Cases - Sukindar; Hendrik Kusnianto; Sarikun; Benhard Kurniawan Pasaribu; Muhd Syahazizamir bin Sahmat (MILRev: Metro Islamic Law Review, 2024)
Religious courts face complex challenges in resolving contemporary cases, such as marital disputes, inheritance distribution, and conflicts in Sharia-based economic matters. In the digital era, Artificial Intelligence (AI) offers innovative solutions to enhance the efficiency and accuracy of legal processes. This study employs a qualitative method with a descriptive-analytical approach to explore the potential use of AI in religious courts. Data was collected through literature reviews and document analysis, focusing on AI applications in inheritance calculations based on Islamic faraidh law, virtual dispute mediation, and Sharia contract analysis. The analysis follows the Miles and Huberman framework, involving data reduction, display, and conclusion drawing. Data validation was carried out through source triangulation to ensure the accuracy and credibility of the findings. The research findings reveal that AI can support digitalizing legal processes in religious courts, such as managing electronic documents, predicting rulings based on legal precedents, and monitoring compliance with sharia principles. Additionally, AI can potentially improve the efficiency of dispute mediation through digital platforms and facilitate automated inheritance calculations in line with Islamic law. However, implementing AI presents challenges, including inadequate regulations, potential algorithmic bias, and compatibility with Islamic legal values. This study’s academic contribution provides a new perspective on integrating modern technology with Islamic law, particularly within the religious court system. The findings are expected to serve as a foundation for developing strategic policies to support AI implementation in Islamic legal systems, addressing societal needs in the contemporary era.